Accumulation of Spliced Avian Retrovirus mRNA Is Inhibited in S-Adenosylmethionine-Depleted Chicken Embryo Fibroblasts - Stoltzfus, C. Martin (1982)
The synthesis and processing of B77 avian sarcoma virus RNA in infected chicken embryo fibroblasts was followed in the presence and absence of cycloleucine, a competitive inhibitor of the synthesis of S-adenosylmethionine and thus an inhibitor of RNA methylations. An increase in the steady-state levels of genome-length RNA and a decrease in the steady-state levels of subgenomic RNA molecules were obtained in the S-adenosylmethionine-depleted avian sarcoma virus-infected cells after 24 h of treatment with the inhibitor. The total number of virus-specific RNA molecules per cell, however, remained relatively constant under either condition. The production of newly synthesized virus-specific RNA in cycloleucine-treated and untreated cells infected with a transformation-defective strain of B77 avian sarcoma virus was followed as a function of [(3)H]uridine labeling time. The accumulation of radioactive genome-length 8.4-kilobase (kb) RNA continued in cycloleucine-treated cells, and virus particle production proceeded at normal rates as previously shown by incorporation of labeled nucleoside precursors or amino acids. In contrast, newly synthesized 3.5-kb subgenomic mRNA, the putative mRNA for the envelope protein precursor, failed to accumulate in the treated cells. The extent of the inhibition in the appearance of the radioactive 3.5-kb RNA was correlated with the extent of the inhibition of viral genomic and cellular mRNA methylations and was a function of the cycloleucine concentration. Under conditions in which the accumulation of 3.5-kb envelope protein mRNA was blocked by the cycloleucine treatment, there were significant increases in the rate of synthesis of the polypeptide products of the genome-length RNA, the precursors to the non-glycosylated gag proteins (Pr76(gag)), and the reverse transcriptase (Pr 180(gag pol)) relative to the rate of synthesis of the envelope protein precursor (gPr 92(env)). These results suggest that there is an S-adenosylmethionine requirement for the splicing, but not for the synthesis, packaging, or messenger function, of avian retrovirus genome-length RNA. Possible reasons for this requirement are discussed.